2007
DOI: 10.1002/yea.1545
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology perspective of wine fermentations

Abstract: The yeast Saccharomyces cerevisiae is an important industrial microorganism. Nowadays, it is being used as a cell factory for the production of pharmaceuticals such as insulin, although this yeast has long been utilized in the bakery to raise dough, and in the production of alcoholic beverages, fermenting the sugars derived from rice, wheat, barley, corn and grape juice. S. cerevisiae has also been extensively used as a model eukaryotic system. In the last decade, genomic techniques have revealed important fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 122 publications
(158 reference statements)
1
48
0
3
Order By: Relevance
“…Numerous genes have been reported to be up-or downregulated, revealing the possible implication of several pathways, such as the regulatory HOG and TOR pathways (8,31), transcription machinery and RNA processing (28), protein trafficking and vacuolar function and transport (5,37), peroxisome import protein machinery (34), and lipid membrane and wall biosynthesis (15). However, most of these studies were centered on active growing cells, with less attention being paid to late stages of fermentation.…”
mentioning
confidence: 99%
“…Numerous genes have been reported to be up-or downregulated, revealing the possible implication of several pathways, such as the regulatory HOG and TOR pathways (8,31), transcription machinery and RNA processing (28), protein trafficking and vacuolar function and transport (5,37), peroxisome import protein machinery (34), and lipid membrane and wall biosynthesis (15). However, most of these studies were centered on active growing cells, with less attention being paid to late stages of fermentation.…”
mentioning
confidence: 99%
“…In fermentation or refermentation, multiple stress conditions are imposed on the yeast cell such as high osmolarity; low pH; sulfur dioxide (SO 2 ); ethanol toxicity; temperature variations; increasing nitrogen limitation; and elevated acetic acid concentrations. All of these stress conditions may lead to reduced cellular growth, cellular death and, consequently, stuck fermentations [14,[66][67][68].…”
Section: Va Bio-reduction By S Cerevisiae Yeasts Strains and Its Limmentioning
confidence: 99%
“…Whole-genome expression profiling can measure the transcriptional gene response to conditions or treatments of interest in a single assay, such as chemical or environmental agents (Jelinsky and Samson 1999;Jelinsky et al 2000;Gasch et al 2000;Hughes et al 2000a;Pizarro et al 2007). In an experiment that studied varied environmental conditions, the authors actually found that while a large set of genes showed similar response to almost all conditions studied, others were specialized for specific responses (Gasch et al 2000).…”
Section: Impact Of Dna Array Technology On Yeast Gene Expression Resementioning
confidence: 96%
“…Given the utility of DNA arrays in investigating how interesting genes change their expression throughout a biological process, several attempts were carried out in wine yeasts at the beginning of the twenty-first century (reviewed in Pérez-Ortín et al 2002b;Pizarro et al 2007). Once more, the yeast S. cerevisiae was the first microorganism in which wild living strains (different from the model strain used for the array probes design) of industrial interest were studied using this powerful technique.…”
Section: Expression Studies Of Wine Yeastsmentioning
confidence: 99%
See 1 more Smart Citation